QUALITATIVE STUDY OF HANDLING PATIENT COMPLAINTS IN HEALTH SERVICES AT INSTALLATIONS OF MAKASSAR CITY REGIONAL HOSPITAL IN 2021 - Musyawir, Andi Herul (Homes Journal: Hospital Management Studies Journal, 2022)
Background: Complaint handling is something that will be carry out by the company when there are complaints from the customers who are satisfied with the service providers or after service failures. Good complaint management as a strategy to improve service and maintain good relationships with customers. Effective complaint manipulation affects not only customers, but will have a major influence on organizations to improve service quality, including cost savings. Objective: This study aims to discover the process of implementation, supporting factors and inhibiting factors of handling complaints in health services at the Inpatient Installation of the Makassar City General Hospital. Method: This study used a qualitative approach method that aims to find out more about the Overview of Patient Complaints Handling in Health Services at the Inpatient Installation of the Makassar City General Hospital in 2021. It was conducted through in-depth interview and observation techniques to informants consisting of the Head of Public Relations, Nurses and Patients. Result: The results showed that the complaint handling process at the Makassar City Hospital was quite good, This was seen from the facilities and infrastructure provided as well as in following up on every incoming complaint. The supporting factor is the existence of SOP, complaint facilities and follow-up, while the inhibiting factor is the number of employees in the field of complaints is still lacking. Suggestion: It is necessary to hold special training for officers in handling complaints so that in the service of patient complaints they can help improve the service quality of Makassar City Hospital.